REDESAIN STRUKTUR GEDUNG ASRAMA PUTRI EMPAT LANTAI UIN MAULANA MALIK IBRAHIM DENGAN METODE SRPMK - Khanifan Fisabila Firdaus (Jurnal Vokasi Teknik Sipil, 2025)
Indonesia is located in an active tectonic plate convergence zone, experiencing a high frequency of earthquakes. In 2023, a total of 10,789 earthquake events were recorded, varying in magnitude and depth, including in Malang, where seismic acceleration ranged from 0.41g to 0.72g, according to data from puskim.pu.go.id. Based on SNI 1726-2019, buildings in earthquake-prone areas must be designed to withstand lateral forces to ensure safety. The implementation of the Special Moment Resisting Frame System (SMRF) with the Strong Column-Weak Beam (SCWB) principle aims to ensure that initial failure occurs in beams rather than columns. In addition to earthquake resistance, structural design efficiency is crucial to achieving a balance between cost and safety. Key factors influencing structural design, such as cross-sectional dimensions, materials, and loads, must be carefully considered. Structural analysis is conducted using ETABS software to determine internal forces based on applied load combinations. The redesign results indicate differences in material requirements for the existing primary beam structure when compared between the redesign and the existing structure. The redesign achieved savings of 18.79% in concrete usage and 20.94% in steel requirements.